MultiResGNet: Approximating Nonlinear Deformation via Multi‐Resolution Graphs. (4th June 2021) - Li, Tianxing; Shi, Rui; Kanai, Takashi
Abstract: This paper presents a graph‐learning‐based, powerfully generalized method for automatically generating nonlinear deformation for characters with an arbitrary number of vertices. Large‐scale character datasets with a significant number of poses are normally required for training to learn such automatic generalization tasks. There are two key contributions that enable us to address this challenge while making our network generalized to achieve realistic deformation approximation. First, after the automatic linear‐based deformation step, we encode the roughly deformed meshes by constructing graphs where we propose a novel graph feature representation method with three descriptors to represent meshes of arbitrary characters in varying poses. Second, we design a multi‐resolution graph network (MultiResGNet) that takes the constructed graphs as input, and end‐to‐end outputs the offset adjustments of each vertex. By processing multi‐resolution graphs, general features can be better extracted, and the network training no longer heavily relies on large amounts of training data. Experimental results show that the proposed method achieves better performance than prior studies in deformation approximation for unseen characters and poses.